PER VAGINAL DELIVERY OF A "DICEPHALUS DICAUDATUS XIPHOPHAGUS" MONSTER - RAVIKUMAR, K; KRISHNAKUMAR, K; NAPOLEAN, R EZAKIAL; CHANDRAHASAN, C (The Indian Journal of Animal Reproduction, 2023)
A rare case of dystocia due to a conjoined twin (Dicephalus Dicaudatus Xiphophag us Monster) in a pluriparousshe buffalo reported.
Keywords: Dicephalus; Dicaudatus; Xiphophagus; Monster; Conjoined twin; Buffalo